PROFITABILITY OF ISLAMIC BANKS: A PANEL DATA ANALYSIS - Bakkeri, Amine; Ali, Abdelhakim Ben (Indian Journal of Finance and Banking, 2020)
This article aims to examine the impact of internal and external factors on the profitability of 30 Islamic banks operating in the Middle East and North Africa over a period from 2005 till 2018. We use the OLS method according to Panel data. Empirical results indicate that the quality of management, liquidity, and capitalization, quality of services, the presence of women and the competence of staff are significant determinants of profitability. The other determinants including diversification, size and inflation have no significant effect on the Islamic banks’ profitability. JEL Classification Codes: G21, G24, C33, D02.